Does Off-farm Employment Enhance the Welfare of Rural Households in Indonesia? - Asih, Dewi Nur (International Journal of Agriculture System, 2024)
This study examines whether taking advantage of off-farm employment as an alternative income source improves the welfare of rural households in Indonesia. Using a panel data set from rural households in Central Sulawesi, the effect of off-farm diversification examines on total household income and economic mobility over time. A fixed effects and random effects model with an instrumental variable is applied in analyzing the causal effects of off-farm employment. The findings confirm substantial growth stemming from work outside of a household’s farming, which is shown to improve income and economic mobility in rural areas. Off-farm work was found to positively affect total household income, which increased by 63.20% in real Indonesia rupiah (IDR) in conjunction with the number of men in the family and cocoa cultivation. The results also indicate a need for a policy that encourages off-farm employment, particularly for value-added activities that are accessible to lower-income groups to improve income and reduce poverty among the poor